PENGARUH PARTISIPASI ANGGARAN, ASIMETRI INFORMASI, TEKANAN ANGGARAN DAN KOMITMEN ORGANISASI TERHADAP SENJANGAN ANGGARAN (Studi Kasus Pada Perusahaan Penerbangan Charter) - Glory Koeswardhana (Journal of Information System, Applied, Management, Accounting and Research, 2017)
This study aims to obtain empirical evidence of whether the participation factors of the budget, information asymmetry, budget emphasis and organizational commitment affect the budget slack. The study was conducted at PT. Pelita Air Service in the month of June to December 2011. Population is the staff and management that are directly related to the preparation of the budget. Randomly selected sample of 117 respondents. Analysis of data using multiple linear regression. The results of this study indicate that the test results the coefficient of determination, adjusted R 2 is equal to 0.714, while the F test results at 62.871 with a significance level of 5%, indicating that /simultaneous participation of the budget, information asymmetry, budget emphasis, and organizational commitment have significant effect on the budget slack. However, partially based on t test with a significance level of 5% and the standardized coefficient 0.386, budgetary participation has a positive effect / direct significant impact on the budget slack; with a standardized coefficient of 0.441 in the direction of the information asymmetry effect / positive significant impact on the budget slack; with standardized coefficient of 0.190 budget emphasis have a positive / direction of the budget slack. While the commitment of the organization, with a standardized coefficient - 0.115 negative effect / no direction to the budget slack. Therefore, corporate management must constantly anticipate and control the budget participation, information asymmetry, budget emphasis to reduce the budget slack.